Fluorescent Red‐Emitting BODIPY Oligofluorene Star‐Shaped Molecules as a Color Converter Material for Visible Light Communications. Issue 4 (12th November 2014) - Sajjad, Muhammad T.; Manousiadis, Pavlos P.; Orofino, Clara; Cortizo‐Lacalle, Diego; Kanibolotsky, Alexander L.; Rajbhandari, Sujan; Amarasinghe, Dimali; Chun, Hyunchae; Faulkner, Grahame; O'Brien, Dominic C.; Skabara, Peter J.; Turnbull, Graham A.; et al.
<x xml:space="preserve">Abstract</x> Star‐shaped organic semiconductors with boron dipyrromethene (BODIPY) cores are color‐conversion materials for blue LED‐based visible light communications. The difference between 0 and 1 bits is resolved in colour‐converted data links at 100 Mb s−1. The BODIPY modulation bandwidth is eight times higher than that measured using conventional phosphor color converters. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>